2022
DOI: 10.1177/11206721221137153
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers predicting central serous chorioretinopathy episode persistence

Abstract: Purpose The purpose of this study was to identify biomarkers at presentation that are associated with a persistent central serous chorioretinopathy (CSC) episode. Methods The prospective study included 35 patients with an acute CSC episode. Potential clinical and imaging biomarkers were evaluated at baseline and 3 months from the episode onset. As biomarkers age, sex, steroid use, episode recurrence, central retinal thickness (CRT), macular volume (MV), choroidal thickness (CT), pigment epithelial detachment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, no differences for HF and FIPED were found between aCSC and cCSC. Previous studies have utilized specific OCT parameters, like increased choroidal thickness (CT), elevated choroidal vascularity index (CVI) and choroidal HF to identify and diagnose CSC [7,8,14,15]. However, no consistent evidence for distinctive OCT biomarkers to establish the CSC diagnosis?…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences for HF and FIPED were found between aCSC and cCSC. Previous studies have utilized specific OCT parameters, like increased choroidal thickness (CT), elevated choroidal vascularity index (CVI) and choroidal HF to identify and diagnose CSC [7,8,14,15]. However, no consistent evidence for distinctive OCT biomarkers to establish the CSC diagnosis?…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have utilized speci c OCT parameters, like increased choroidal thickness (CT), elevated choroidal vascularity index (CVI) and choroidal HF to identify and diagnose CSC (7,8,14,15). However, no consistent evidence for distinctive OCT biomarkers to establish the CSC diagnosis?…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously examined the predictive role of retinal biomarkers in CSC. [17][18][19] In a recent study, Singh et al analyzed the imaging biomarkers in a large sample (n = 231 of 201 patients with CSC) for the prediction of the disease clinical course. They found that the resolution of the disease was correlated with changes in central macular thickness and subfoveal choroidal thickness, whereas modifications in visual acuity at 12 months were associated with SRF height.…”
Section: Discussionmentioning
confidence: 99%